TLR3 Expression is a Potential Prognosis Biomarker and Shapes the Immune-Active Tumor Microenvironment in Esophageal Squamous Cell Carcinoma - Su R; Cai L; Xiong P; Liu Z; Chen S; Liu X; Lin R; Lei Z; Tian D; Su M (Dove Medical Press, 2022)
Ruibing Su,1,* Lijun Cai,1,* Pan Xiong,1,* Zhiwei Liu,1,* Shaobin Chen,2 Xi Liu,1 Runhua Lin,1 Zhijin Lei,1 Dongping Tian,1 Min Su1 1Institute of Clinical Pathology, Department of Pathology, Shantou University Medical College, Shantou, Guangdong, People's Republic of China; 2Department of Thoracic Surgery, Cancer Hospital of Shantou University Medical College, Shantou, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Min Su, Institute of Clinical Pathology, Department of Pathology, Shantou University Medical College, No. 22 Xinling Road, Shantou, Guangdong, People's Republic of China, Tel/Fax +86-754-88900429, Email minsu@stu.edu.cnBackground: Toll-like receptor 3 (TLR3) not only plays a crucial role in innate immune and inflammation but also in anti-cancer immunity. Nevertheless, the clinicopathological outcome of TLR3 in ESCC is still ambiguous.Methods: Immunohistochemistry was performed to investigate TLR3 expression and its impact on survival in 137 ESCC patients (including paired esophageal tissues with different stages of early lesions from 37 patients). Furthermore, we downloaded ESCC RNA-seq datasets (including phenotype and survival data) from The Cancer Genome Atlas (TCGA). The relationship between TLR3 and prognosis, biological landscape, and immune infiltration was assessed to verify the immunohistochemical results of our tissue samples, explore the possible mechanism of prognostic outcomes, and predict the sensitivity of immunotherapy.Results: TLR3 protein expression displayed an increasing trend in the progression through different grades of cellular atypia, from normal, esophageal simple hyperplasia (ESSH), intraepithelial neoplasia (IEN) to ESCC (P < 0.0083). TLR3 protein had a positive association with inflammation level (Rho = 0.341, P < 0.001). TLR3 mRNA expression was significantly higher in comparison to adjacent normal tissues (P < 0.001). Cox regression analysis indicated high TLR3 protein and mRNA expression conferred good prognosis in our samples and TCGA, especially for advanced ESCC patients (TNM stage III and IV). Overexpression of TLR3 resulted in an immune-active microenvironment via the recruitment of immune-active cells including cytotoxic lymphocytes (CTLs), CD8+ T cells, NK cells, dendritic cells, and M1-type macrophages. TLR3 expression was correlated with the pro-inflammatory cytokines and chemokines relating to anti-tumor immunity. Moreover, GSEA analysis indicated upregulated expression of TLR3 could activate the apoptotic pathway.Conclusion: High TLR3 expression in ESCC patients was associated with a more favorable prognosis, immune-active cell infiltration, and an activated apoptotic pathway. TLR3 has potential applications for immunotherapy and immune response prediction in patients with ESCC.Keywords: esophageal squamous cell carcinoma, TLR3, prognosis, immune infiltrates, immunotherapy response